2014
DOI: 10.1371/journal.ppat.1004407
|View full text |Cite
|
Sign up to set email alerts
|

A Relay Network of Extracellular Heme-Binding Proteins Drives C. albicans Iron Acquisition from Hemoglobin

Abstract: Iron scavenging constitutes a crucial challenge for survival of pathogenic microorganisms in the iron-poor host environment. Candida albicans, like many microbial pathogens, is able to utilize iron from hemoglobin, the largest iron pool in the host's body. Rbt5 is an extracellular glycosylphosphatidylinositol (GPI)-anchored heme-binding protein of the CFEM family that facilitates heme-iron uptake by an unknown mechanism. Here, we characterize an additional C. albicans CFEM protein gene, PGA7, deletion of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 63 publications
4
110
1
Order By: Relevance
“…Our studies reveal two faces of host Cu during infection with C. albicans: while serum Cu elevates, Cu can become limiting at the major site of infection in the kidney. As one possibility, the host may intentionally restrict Cu as part of an innate nutritional immunity response, similar to host withholding of Fe, Mn, and Zn for invading microbes (3)(4)(5)(6)(7)(8)(9)(10). Recent studies by Brown and colleagues have shown that during C. albicans infection of the kidney, Fe moves away from sites of fungal lesions in the cortex to the medulla as an apparent mechanism for Fe withholding (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies reveal two faces of host Cu during infection with C. albicans: while serum Cu elevates, Cu can become limiting at the major site of infection in the kidney. As one possibility, the host may intentionally restrict Cu as part of an innate nutritional immunity response, similar to host withholding of Fe, Mn, and Zn for invading microbes (3)(4)(5)(6)(7)(8)(9)(10). Recent studies by Brown and colleagues have shown that during C. albicans infection of the kidney, Fe moves away from sites of fungal lesions in the cortex to the medulla as an apparent mechanism for Fe withholding (9).…”
Section: Resultsmentioning
confidence: 99%
“…As part of the innate immune response, the host deliberately withholds metals, such as Fe, Zn, and Mn, from invading microbes in a process known as "nutritional immunity" (3)(4)(5). Like other infectious agents, C. albicans is equipped to handle restrictions placed on these micronutrients and can activate diverse pathways for scavenging host sources of Fe and Zn (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…A new haembinding protein, Pga7, a member of the common fungal extracellular membrane (CFEM) family, has recently been reported in Candida albicans and contributes to virulence in a mouse model. In vitro, both Rbt5 and Pga7 extract haem from haemoglobin, and haem can be rapidly transferred between these two CFEM proteins (Kuznets et al, 2014). Candida albicans also produces the haemolytic molecule mannan which facilitates access to haembound iron (Tanaka et al, 1997;Watanabe et al, 1999).…”
Section: Haem Uptake Systemsmentioning
confidence: 99%
“…Therefore, future anti-C. albicans therapies may also include the reconstruction of physiologically relevant pH values and CO 2 concentrations at the sites of infections to prevent or at least hinder the spread of Candida cells toward deeper tissues. Another therapeutic approach may rely on the disturbance of the hemoglobin and hemin uptake by C. albicans through hemoglobin/heme-binding receptors on the surface of Candida cells [32,70,71], which may also reduce the virulence of C. albicans [33]. It is worth noting that the dimorphic morphological transitions of C. albicans is an extensive studied area in fungal biology and are considered as promising targets in future antifungal drug research [72].…”
Section: Discussionmentioning
confidence: 99%
“…In the human body, iron is present exclusively in bound forms, e.g., in hemoglobin, transferrin, and ferritin [14,[27][28][29][30]. Nevertheless, C. albicans has a remarkable arsenal to extract iron from its hosts, including the internalization and degradation of hemoglobin and hemin [14,28,[31][32][33]. In the circulating blood, free hemoglobin and hemin cannot be found under normal physiological conditions due to the hemoglobin-binding and heme-binding capacities of haptoglobin and hemopexin, respectively [18].…”
Section: Introductionmentioning
confidence: 99%